Beasts of the earth : animals, humans, and disease - Torrey, E. Fuller (Edwin Fuller), 1937-; Yolken, Robert H. (Rutgers University Press, 2005)
Humans have lived in close proximity to other animals for thousands of years. Recent scientific studies have even shown that the presence of animals has a positive effect on our physical and mental health. People with pets typically have lower blood pressure, show fewer symptoms of depression, and tend to get more exercise. But there is a darker side to the relationship between animals and humans. Animals are carriers of harmful infectious agents and the source of a myriad of human diseases. In recent years, the emergence of high-profile illnesses such as AIDS, SARS, West Nile virus, a.